PENGARUH LATIHAN PAC-MAN TERHADAP KETERAMPILAN PASSING PADA PEMAIN BOLA SSB TARUNA MERPATI PEKANBARU - Ronal Ray Fatma; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
ABSTRACT : The problem in this research is the lack of ability of the players shot accuracy and many kicks are not the right target. The research objective was to determine whether there are Influence Of Practice Ball Pac-Man Toward The Accuracy Kick In Soccer Players SSB Taruna Merpati Pekanbaru. This research is experiment. The population in this research are as many as 14 people. Relative to the population that is not so much and are still in the ability of the researcher, the entire population sampled thus the total sample in this research amounts to 14 people. Instruments using in this research is a test shoot or kick the ball to a target aims to measure the accuracy of the kick. After that pre-test and handing practice pac-man during 16 sessions to 14 students SSB Taruna Merpati Pekanbaru and the continue with post test. Processing data using statistical, normality test with Lilliefors test at significant level a = 0.05. Hypothesis is the influence of exercise Pac-Man to a skill Passing the football players SSB Taruna Merpati Pekanbaru. Based on the analysis of statistical data are the average pre-test of 11.50 and an average post-test of 14.07, then the data is normal. Based on t test analysis produces thitung 5.810 > ttabel 1.771 a = 0.05, thus it can be concluded there is the influence of exercise Pac-Man against passing skills on the football players SSB Taruna Merpati Pekanbaru.Keywords: Pac-Man, accuracy Passing